Simulation and Construction of Voltage Sag Corrector - Rohi, Daniel (2002)
Electrical power quality has been the most important issue in recent years. Research has shown that nearly 92% of the electrical power quality problems were associated with voltage sags. Voltage sag is a short duration reduction in rms voltage caused by short circuit faults, switching operations, impact over loading, or starting of large motors. To mitigate voltage sag problems are to have a cautious maintenance and control to the supply, transmissions and the distribution to prevent damages. User can find the underlying cause of voltage sag by installing devices that can minimize voltage sag. Electro-magnetic contactor is one of the devices that is sensitive to voltage sag. Data shows that contactor, which is widely used for controlling motor, cannot work properly when there are 50% rms voltage reduction for a period longer than one cycle. This project will describe a type of voltage sag corrector (VSC) device that is especially use to minimize voltage sag impact at the contactor. The VSC device is used for contactor that uses 120V AC. To give enough magnetic power to the contactor, AC voltage that is stable is used until there is a match w ith DC voltage. When there is 120 V AC input, it will be converted by the rectifier to DC voltage with a value of 170 V. Furthermore, 170 V DC w i l l be reduce to 12 V DC by the chopper circuit. The chopper circuit is driven by the output signal or duty cycle of the control circuit. The duty cycle depends on the occurring voltage sag magnitude. The duty cycle will increase proportional with voltage sag. The software Orcad PSpice version 9.1 is effective to make simulations of the VSC circuit. The experimental result shows that the VSC is effective to mitigate voltage sag for contactor ride-through.